2018
DOI: 10.1016/j.athoracsur.2018.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of Endoscopic Thoracic Sympathectomy for Primary Palmar Hyperhidrosis

Abstract: This study confirms that the benefits of ETS are maintained in the long term. Although CS is the main cause for discontent postoperatively, it is still preferred over the distress experienced from palmar or axillary hyperhidrosis and QOL is increased despite CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 9 publications
0
29
0
1
Order By: Relevance
“…A common clinical scenario involves a sympathetic trunk rupture from a thoracic or lumbar sympathectomy, performed by mainly regional hyperhidrosis treatment, also for nerve regeneration, pain control, and ischemic leg prevention. [10][11][12][13] The main challenge with the reconstruction of the ruptured sympathetic trunk is because sympathetic trunk is located deep within the thoracic cage near the spine, and posterior to the heart, aorta, and lung, hence creating a difficult and dangerous approach. From literature review, the sympathetic nerve reconstruction (STR) could be traced back to 1998, where an open thoracotomy was used by Telaranta.…”
mentioning
confidence: 99%
“…A common clinical scenario involves a sympathetic trunk rupture from a thoracic or lumbar sympathectomy, performed by mainly regional hyperhidrosis treatment, also for nerve regeneration, pain control, and ischemic leg prevention. [10][11][12][13] The main challenge with the reconstruction of the ruptured sympathetic trunk is because sympathetic trunk is located deep within the thoracic cage near the spine, and posterior to the heart, aorta, and lung, hence creating a difficult and dangerous approach. From literature review, the sympathetic nerve reconstruction (STR) could be traced back to 1998, where an open thoracotomy was used by Telaranta.…”
mentioning
confidence: 99%
“…Just after the TS patients are pleased as they do not longer sweat in the areas where it was incredibly cumbersome (hands and axillae) [9], but as time goes by, especially during the summer, they notice sweating in areas that did not sweat before or not to such an extent, such as the abdomen, torso, buttocks, and thighs [10]. This new sweating is known as compensatory hyperhidrosis (CH) and is the fundamental cause of long-term patients' dissatisfaction [11][12][13]. Another problem, although patients do not complain so often about it [14], is the over-dryness of the sympathetically denervated area (head/face, hands, and axillae) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although conservative treatments may be tried first, most patients resort to surgical treatment due to such reasons as the side effects of the treatments, the short duration of action, and unsatisfactory outcomes. [1][2][3][4][5][6][7] Previous studies have identified endoscopic thoracic sympathicotomy (ETS) as an effective method for the treatment of both palmar and axillary hyperhidrosis (PH and AH). Questionnaires evaluating postoperative quality of life have reported success rates exceeding 90%, especially for PH.…”
Section: Introductionmentioning
confidence: 99%